A world of taxonomic pain: cryptic species, inexplicable host-specificity, and host-induced morphological variation among species of Bivesicula Yamaguti, 1934 (Trematoda: Bivesiculidae) from Indo-Pacific Holocentridae, Muraenidae and Serranidae. Issue 6 (10th May 2022) - Cribb, Thomas H.; Bray, Rodney A.; Justine, Jean-Lou; Reimer, James; Sasal, Pierre; Shirakashi, Sho; Cutmore, Scott C.
Abstract: Abstract: The taxonomy of species of Bivesicula Yamaguti, 1934 is analysed for samples from holocentrid, muraenid and serranid fishes from Japan, Ningaloo Reef (Western Australia), the Great Barrier Reef (Queensland), New Caledonia and French Polynesia. Analysis of three genetic markers ( cox 1 mtDNA, ITS2 and 28S rDNA) identifies three strongly supported clades of species and suggests that Bivesicula as presently recognized is not monophyletic. On the basis of combined morphological, molecular and biological data, 10 species are distinguished of which five are proposed as new. Bivesicula Clade 1 comprises seven species of which three are effectively morphologically cryptic relative to each other; all seven infect serranids and four also infect holocentrids. Bivesicula Clade 2 comprises three species of which two are effectively morphologically cryptic relative to each other; all three infect serranids and one also infects a muraenid. Bivesicula Clade 3 comprises two known species from apogonids and a pomacentrid, and forms a clade with species of Paucivitellosus Coil, Reid & Kuntz, 1965 to the exclusion of other Bivesicula species. Taxonomy in this genus is made challenging by the combination of low resolving power of ribosomal markers, the existence of regional cox 1 mtDNA populations, exceptional and unpredictable host-specificity and geographical distribution, and significant host-induced morphological variation.